Mental health and well-being in animals - McMillan, Franklin D (CABI, 2020)
"The second edition is fully revised, expanded, and comprehensively updated with the most current knowledge about the full array of mental health issues seen in animals.Written by key opinion leaders, internationally-recognized experts and specialists, it is comprehensive covering basic principles to mental wellness, emotional distress, suffering and mental illness, through to measurement and treatment. With even more practical information and clinical pearls, this book remains invaluable to veterinary professionals, animal welfare researchers and advocates, and other animal caregivers"--